A new large-bodied, rupicolous Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) allied to Cnemaspis heteropholis Bauer, 2002 from the Central Western Ghats of Karnataka, India - Khandekar, Akshay; Thackeray, Tejas; Pal, Saunak; Agarwal, Ishan (Zootaxa, 2020)
We describe a new large-bodied, rupicolous Cnemaspis from near Sakleshpur in the Central Western Ghats of Karnataka, India. Cnemaspis magnifica sp. nov. is allied to C. heteropholis and can be diagnosed from all other Indian Cnemaspis by the absence of spine-like scales on flank; heterogeneous dorsal pholidosis, presence of only femoral pores in males, homogenous dorsal pholidosis of tail with small, smooth, regularly arranged, flattened, subimbricate scales, without whorls of enlarged tubercles, median row of sub-caudals enlarged and smooth. The new species differs from its closest congener C. heteropholis in body size, the number of longitudinal ventral scales, number of lamellae under digit I and IV of manus and pes, and subtle colour pattern differences; besides 9.1 % uncorrected ND2 sequence divergence. We provide the first description of topotypic male of C. heteropholis along with data on its distribution and natural history. The discovery of Cnemaspis magnifica sp. nov. with minimal field survey effort indicates the need for further herpetological exploration in the region.